Investigating Users' Natural Engagement with a 3D Design Approach in an Egocentric Vision Scenario - de Oliveira, Eder; Clua, Esteban Walter Gonzalez; Trevisan, Daniela Gorski; Salgado, Luciana Cardoso de Castro (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
User interfaces based on modalities such as touch, gestures or voice are often referred to as Natural User Interfaces (NUI). Particularly, gesture interactions have become an adequate form of interaction on touch devices, due well established conventions for gestures in real life. In virtual and augmented reality, gestures are also a very natural way to interact with digital objects, but there is a lack of clear guidelines for how to design gesture-based interaction in AR and VR. This work presents an approach based on user centered design for the usage of bare hands to control an immersive system using commercial low-end HMD's from an egocentric perspective and built from a proposed case study methodology. Our design approach generated an interaction vocabulary, considering users' preferences, seeking a set of natural and comfortable hand poses and evaluated users' satisfaction and performance.